Information Retrieval in Text-Based Document using Boyer Moore Algorithm - Yudhi Setyo Purwanto; M. Farid Rifai; Hendra Jatnika; Gina Afra Ardelia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The Language Development Center (LDC) is a language laboratory that annually serves more than 1000 participants in activities such as standardized tests and language courses for students and lecturers. This activity generates a lot of data which is still managed ineffectively and causes several problems in data retrieval, archiving, and monitoring. Therefore, this research was made with the aim of creating a system so that data management in LDC becomes more effective. In designing and building this system, the writers uses the Waterfall method and also implements the Boyer Moore algorithm in the data search process. Boyer moore algorithm helps the data search process more effectively and can search for words in several text-based files at once. The result of this research is a web-based data management information system that makes the data management process becomes more effective and efficient. Keywords: information system, data management, data retrieval, Boyer Moore algorithm